2009
DOI: 10.1002/chin.200913186
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Lanostane‐Type Triterpenoids from the Sclerotia of Inonotus obliquus Possessing Antitumor Promoting Activity.

Abstract: Terpenes U 0200 Lanostane-Type Triterpenoids from the Sclerotia of Inonotus obliquus Possessing Antitumor Promoting Activity. -(TAJI, S.; YAMADA, T.; WADA, S.-I.; TOKUDA, H.; SAKUMA, K.; TANAKA*, R.; Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Polysaccharides, such as water soluble intracellular polysaccharides (IPSWs), homogenous polysaccharides (PIP 1 ), and heteropolysaccharides (PIP60-1), have been reported to exert anti-cancer, anti-diabetes, antiinflammation and antioxidation effects (Jang et al, 2004;Hwang et al, 2005). Triterpenoids play an important role in antitumor, anti-inflammation, and immune regulatory properties (Taji et al, 2008;Wang et al, 2009). Moreover, S. sanghuang is one of the rare fungi that contains flavone compounds, which have antioxidation and antitumor effects (Feng et al, 2012;Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides, such as water soluble intracellular polysaccharides (IPSWs), homogenous polysaccharides (PIP 1 ), and heteropolysaccharides (PIP60-1), have been reported to exert anti-cancer, anti-diabetes, antiinflammation and antioxidation effects (Jang et al, 2004;Hwang et al, 2005). Triterpenoids play an important role in antitumor, anti-inflammation, and immune regulatory properties (Taji et al, 2008;Wang et al, 2009). Moreover, S. sanghuang is one of the rare fungi that contains flavone compounds, which have antioxidation and antitumor effects (Feng et al, 2012;Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…4 It produces a diverse range of metabolites, which are biologically active compounds possessing hypoglycemic, 5 hepatoprotective, 6 anti-fungal, and antitumor activities. 2,[7][8][9] In Vitro Antitumor Activity and Structure Characterization of Ethanol Extracts from Wild and Cultivated Chaga Medicinal Mushroom, Inonotus obliquus (Pers.:Fr.) Pilát (Aphyllophoromycetideae) Kukulyanskaya et al 10 reported that Chaga produces a diverse range of phenolic constituents including hispidin analogs and melanins.…”
Section: Introductionmentioning
confidence: 99%
“…The research reports on the chemical constituents and pharmacological activities of Inonotus obliquus are also increasing. Inonotus obliquus contains a variety of chemical constituents 8 , the main compounds are triterpenes 9 , polysaccharides 10 , and sesquiterpenes 11 . A new compound (1-(4-hydroxyphenyl)-3-methoxypropan-1-one) (Fig.…”
Section: Introductionmentioning
confidence: 99%